Exploring the power of emotional intelligence: a comprehensive evaluation of its impact on the clinical competence of nursing students - Kholoud Alharbi (BMC Nursing)
Abstract Background Emotional intelligence incorporates important aspects of human connections to develop self-management ability which can boost individual performance. However, existing literature lacks a comprehensive assessment of how emotional intelligence specifically impacts the clinical competence of nursing students. Therefore, the purpose of this study was to determine how emotional intelligence could positively influence the clinical competence of nursing students, ultimately leading to their success. Method A cross-sectional study was conducted on a convenience sample of 181 nursing students. The Schutte Self-Report Emotional Intelligence Test was used to measure the emotional intelligence of students; and Clinical Competence Questionnaire were used to measure the clinical competence of students. Necessary statistical analyses were run using SPSS. Results Findings indicate a moderate level of emotional intelligence among nursing students 130.4 (SD = 35.4); and moderate level of clinical competence among nursing students 186.8 (SD = 49.7). The results revealed there was a correlation between students’ level and emotional intelligence scores; and students’ level and clinical competence scores. There was a strong positive correlation between emotional intelligence and clinical practice scores. Multiple linear regression showed the following predictors for emotional intelligence: students’ level and course; and the following predictors for clinical competence: course, level, and emotional intelligent. Conclusion Emotional intelligence is a crucial aspect in the success and performance of nursing students. Further research studies in multi-geographical areas are required to compare and confirm the findings of the study. Clinical relevance Emotional intelligence in nursing refers to a nurse’s ability to comprehend, use, and manage their emotions in ways that encourage successful communication and conflict resolution. Emotional intelligence can assist nurses create a better rapport with patients, which will improve their hospital experience and make them feel well cared for. Emotional intelligence is also vital for self-motivation and building relationships. Clinical trial number Not applicable.